Ferroptosis Activation Scoring Model Assists in Chemotherapeutic Agents’ Selection and Mediates Cross-Talk With Immunocytes in Malignant Glioblastoma - Wang, Zeyu; Dai, Ziyu; Zheng, Lifu; Xu, Binyuan; Zhang, Hao; Fan, Fan; Zhang, Xun; Liang, Xisong; Liu, Zhixiong; Yang, Kui; Cheng, Quan (Frontiers in Immunology, 2022)
Gliomas are aggressive tumors in the central nervous system and glioblastoma is the most malignant type. Ferroptosis is a programmed cell death that can modulate tumor resistance to therapy and the components of tumor microenvironment. However, the relationship between ferroptosis, tumor immune landscape and glioblastoma progression is still elusive. In this work, data from bulk RNA-seq analysis, single cell RNA-seq analysis and our own data (the Xiangya cohort) are integrated to reveal their relationships. A scoring system is constructed according to ferroptosis related gene expression, and high scoring samples resistant to ferroptosis and show worse survival outcome than low scoring samples. Notably, most of the high scoring samples are aggressive glioblastoma subtype, mesenchymal and classical, by calculating RNA velocity. Cross-talk between high scoring glioblastoma cells and immunocytes are explored by R package ‘celltalker’. Ligand-receptor pairs like the TRAIL or TWEAK signaling pathway are identified as novel bridges implying how ferroptosis modulate immunocytes’ function and shape tumor microenvironment. Critically, potential drugs target to high scoring samples are predicted, including SNX2112, AZ628 and bis(maltolato)oxovanadium(IV) and five compounds from CellMiner database. Taken together, ferroptosis associates with glioblastoma aggressiveness, cross-talk with immunocytes and offer novel chemotherapy strategy.